Clinical implications of the genetics of sporadic colorectal cancer. Issue 10 (28th March 2019) - Fischer, Jesse; Walker, Logan C.; Robinson, Bridget A.; Frizelle, Frank A.; Church, James M.; Eglinton, Tim W.
Abstract : Colorectal cancer (CRC) is common and at least 80% of cases are sporadic, without any significant family history. Prognostication and treatment have been relatively empirical for what has become increasingly identified as a genetically heterogeneous disease. There are three main genetic pathways in sporadic CRC: the chromosomal instability pathway, the microsatellite instability pathway and the CpG island methylator phenotype pathway. There is significant overlap between these complex molecular pathways and this limits the clinical application of CRC genetics. Recent Australian and New Zealand guidelines recommend routine testing of mismatch repair (MMR) status for new cases of CRC and selective KRAS and BRAF testing on the basis of diagnostic, prognostic and therapeutic implications. It is important that all clinicians treating CRC have an understanding of the importance of and basis for identifying key genetic features of CRC. It is likely that in the future better molecular characterization such as that allowed by the consensus molecular subtype classification will allow improved prognostication and targeted therapy in order to deliver more personalized treatment for CRC. Abstract : The genetics of sporadic colorectal cancer have a growing role in the management of patients with the disease. We review the clinically relevant genetic pathways and discuss the clinical implications in the context of recent guidelines for molecular testing in colorectal cancer.